Effect of Alcoholic Extract and Nano-capsules of Bacopa Monnieri Plant on Eggs of the Callosobruchus maculatus - Ali, Zahraa Kareem; Kathier, Sahar Abd (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
This study used wild barbines  (Bacopa Monnieri)  to control the southern cowpea beetle (Callosobruchus maculatus) and their effects on cowpea beetle eggs. Alcoholic extracts and nanocapsules were used at different concentrations, with the alcohol extract being 1000, 2000, and 3000 PPM. Eight out of ten eggs were unhatched, and two hatched, indicating that the 3000 concentrations had the highest egg toxicity rate. Regarding saponins at the same concentrations, the 3000 concentrations had the best results, whereas the 1000 and 2000 concentrations produced poorer results. Additionally, it was discovered that saponins had a stronger effect than terpenes. The nanocapsule concentrations that affected the Callosobruchus maculatus beetle's eggs were 80, 100, 120, and 140. The results showed that the alcoholic extract at different concentrations and times had a greater effect than the nanocapsules. The nanocapsules also had an effect, but it was slightly slower than the alcoholic extract, and the effect increased with increasing time. The effect was found to be highest at a concentration of 140 and lowest at 80 on the eggs of Callosobruchus maculatus.